What moves large grazers? Habitat preferences and complementing niches of large herbivores in a Danish trophic rewilding area - Bent Johann Rech; Robert Buitenwerf; Roberto Ruggiero; Jonas Trepel; Matthias Waltert; Jens-Christian Svenning (Environmental Management, 2025)
Large herbivores (≥45 kg) fulfill key ecological functions. Since the Late Pleistocene megafauna diversity and abundances have declined sharply, with profound consequences for ecosystems. On this background the concept of trophic rewilding has emerged and is increasingly applied to restore natural disturbance regimes and trophic interactions, ultimately aiming to recreate self-sustaining, dynamic and diverse ecosystems. Effects of such efforts (e.g., more heterogeneous habitats) are evident, but herbivore space use, and the resulting distribution of effects on vegetation remain poorly understood. Here, we examine habitat selection of semi-feral water buffalos ( Bubalus bubalis ), horses ( Equus ferus ) and cattle ( Bos taurus ) in a Danish rewilding area. We modelled space use with remote sensed covariates, reflecting resources (vegetation greenness, distance to water) and infrastructure (distances to fences, paths, shelter). Seasonal differences and former land use were tested separately. We found large-herbivore space use to shift seasonally, reflecting food and water availability, and to be influenced by infrastructure and former land use. Horses reacted less to vegetation greenness and water than the two bovids. Cattle selected for green vegetation in summer, while buffalos showed the strongest association with water bodies. Overall, the three semi-feral herbivore species diverged in their habitat use both spatially and seasonally. This can be expected to translate to variable and complementary ecological impacts such as grazing, physical disturbances and habitat engineering. Such variable space use likely increases habitat heterogeneity and species richness. We therefore suggest that a diverse large-herbivore guild is key, both to understanding megafauna ecology and for successful rewilding efforts.

Cardiorespiratory coupling in mechanically ventilated patients studied via synchrogram analysis - Davide Ottolina; Beatrice Cairo; Tommaso Fossali; Claudio Mazzucco; Antonio Castelli; Roberto Rech; Emanuele Catena; Alberto Porta; Riccardo Colombo (Medical & Biological Engineering & Computing, 2023)

2-Phenyl-3-(phenylselanyl)benzofuran elicits acute antidepressant-like action in male Swiss mice mediated by modulation of the dopaminergic system and reveals therapeutic efficacy in both sexes - Taís da Silva Teixeira Rech; Amália Gonçalves Alves; Dianer Nornberg Strelow; Letícia Devantier Krüger; Luiz Roberto Carraro Júnior; José Sebastião dos Santos Neto; Antonio Luiz Braga; César Augusto Brüning; Cristiani Folharini Bortolatto (Psychopharmacology, 2021)

Role of alpha- and beta-adrenoreceptors in rat monocyte/macrophage function at rest and acute exercise - Juliane da Silva Rossato; Mauricio Krause; Augustus Joli Martins Fernandes; João Roberto Fernandes; Isis Lenhard Seibt; Anderson Rech; Paulo Ivo Homem de Bittencourt (Journal of Physiology and Biochemistry, 2014)